Gender Differences in the Treatment of Non–ST‐Segment Elevation Myocardial Infarction - Tavris, Dale (Clin Cardiol, 2010)
BACKGROUND: Women are at greater risk for worse outcomes associated with acute coronary syndrome (ACS) than are men. One explanation may be that they tend to be treated less aggressively than men even when more aggressive treatment is warranted. The purpose of this analysis was to assess this issue. METHODS: We used the Can Rapid Risk Stratification of Unstable Angina Patients Suppress Adverse Outcomes with Early Implementation (CRUSADE) Quality Improvement Initiative registry, an observational data collection that began in November 2001, with retrospective data collection from January 2001 to December 2006. A total of 32 888 subjects met the inclusion/exclusion criteria for our study, based on strong biochemical evidence of myocardial infarction and acute onset of typical cardiac chest pain. We stratified subjects into 16 cells for coronary intervention, based on 4 age groups and 4 cardiac catheterization findings (insignificant, 1‐vessel disease, 2‐vessel disease, 3‐vessel disease). We also stratified subjects into 20 cells for medical treatment, based on 4 age groups and 5 medical treatments. In each cell we compared the rate of coronary intervention (coronary artery bypass grafting or percutaneous coronary intervention) or medical treatment (glycoprotein IIb/IIIa inhibitors, aspirin, clopidogrel, β‐blocker, and statins) for men vs women. RESULTS: Men demonstrated significantly higher rates (P < 0.05) of coronary intervention in 7 of the 16 cells and 9 of the 20 medical treatment cells, compared to no cells in which women had statistically higher rates than men. CONCLUSION: These findings suggest that men are more likely than women to receive coronary intervention and to be medically treated when presenting with evidence of non–ST‐segment myocardial infarction, controlled for age, cardiac catheterization findings, and biochemical evidence of myocardial infarction. Copyright © 2010 Wiley Periodicals, Inc.